Pengelolaan dan Pengawasan Dana Desa dalam Pembangunan Infrastruktur Desa Baru (Jurnal Sosial Humaniora dan Pendidikan, 2026)
Abstract : This study aims to analyze the management and supervision of village fund allocation in infrastructure development in Desa Baru, Pancur Batu Subdistrict, Deli Serdang Regency in 2023. The research method used is a qualitative approach with data collection techniques including observation, interviews, and documentation. The results showed that the management of village funds was carried out in a participatory and transparent manner, but there were still challenges such as low community participation, limited human resources among village officials, and unequal distribution of development. The village government has made improvements such as technical training, strengthening coordination, and increasing community empowerment. This study concludes that strengthening technical capacity and increasing community involvement are essential to achieving equitable and sustainable development. Keywords: Village Fund;Infrastructure; Management;Supervision